Conceptualising and mapping polarisation trends in land systems - Christian Levers; Julian Helfenstein; Matthias Bürgi; Niels Debonne; Vasco Diogo; Rebekka Dossche; Felix Herzog; Yafei Li; Franziska Mohr; Rebecca Swart; Tim G. Williams; Peter H. Verburg (Ambio, 2026)
Polarisation is a key process in land systems, describing land-change trajectories within a region that simultaneously move in opposite directions, such as co-occurring agricultural intensification and abandonment. Land-system polarisation relates strongly to sustainability goals, with potentially positive or negative consequences depending on domain and context. Yet, we lack approaches for mapping polarisation, limiting our understanding of its spatiotemporal distribution and integration into policy or impact assessments. We address this gap by exploring the concept of land-system polarisation and identifying five key dimensions for its mapping: spatial scales, temporal scales, land-use sectors, indicators, and neighbourhood relationships. We propose and test a workflow using the EU’s crop production systems, showing that ~ 87% of NUTS2 regions display polarisation. Our transferable workflow is adaptable across scales and contexts, enabling polarisation to serve as a lens for examining land-change drivers and impacts and providing spatially explicit information to guide targeted intervention and monitoring efforts.